2023
DOI: 10.1021/acssuschemeng.3c01943
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Robust Paper-Based Electronics by Adapting Conventional Paper Making and Coupling with Wet Laser Writing

Abstract: Paper offers the potential as a sustainable substrate for electronics, yet a key remaining challenge is patterning. While most demonstration studies pattern by printing conducting inks onto cellulose, we adapt conventional paper making to create a stable non-conducting composite of graphene oxide (GO; 30%) and cellulose (70%) and then pattern this composite using wet laser writing. Specifically, the GO/cellulose composite is as follows: soaked in a HAuCl 4 solution; laser patterned to simultaneously reduce GO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…One study reported paper made from CF/GO/cellulose, whereby to enable the assembly of GO sheets onto the surface of the cellulose fibers, cationic polyacrylamide (CPAM) was used to control the interfacial interactions. 70 In same study, high-performance, long-lasting paper-based sensors for portable electrochemical detection were demonstrated. 70 In another study, a lens-free optofluidic plasmonic sensor was used for the real-time and label-free monitoring of molecular binding events over a wide field-of-view.…”
Section: Methodologies For Wearable Biosensor Devices and Associated ...mentioning
confidence: 91%
See 1 more Smart Citation
“…One study reported paper made from CF/GO/cellulose, whereby to enable the assembly of GO sheets onto the surface of the cellulose fibers, cationic polyacrylamide (CPAM) was used to control the interfacial interactions. 70 In same study, high-performance, long-lasting paper-based sensors for portable electrochemical detection were demonstrated. 70 In another study, a lens-free optofluidic plasmonic sensor was used for the real-time and label-free monitoring of molecular binding events over a wide field-of-view.…”
Section: Methodologies For Wearable Biosensor Devices and Associated ...mentioning
confidence: 91%
“…70 In same study, high-performance, long-lasting paper-based sensors for portable electrochemical detection were demonstrated. 70 In another study, a lens-free optofluidic plasmonic sensor was used for the real-time and label-free monitoring of molecular binding events over a wide field-of-view. 71 Also, Roy et al developed screen-printed microfluidic technology to monitor diabetic foot ulcers using a portable potentiostat (DFU).…”
Section: Methodologies For Wearable Biosensor Devices and Associated ...mentioning
confidence: 91%
“…Wang et al. [ 173 ] integrated writing strategies to fabricate electrochemical sensors made of gold, by laser‐induced reduction of HAuCl 4 over GO‐modified paper substrates and subsequent electroless Au growth, envisioning R2R fabrication strategies based on this DLW setup. The authors demonstrated the capability of fabricated sensors for hydrogen peroxide detection in milk samples.…”
Section: Dlw‐enabled Electronicsmentioning
confidence: 99%
“…[124] However, other formulations using gelatine matrices have also been employed. [162,163] Several metallic salts have been used for this purpose, including metal nitrates, chlorides and acetates, such as AgNO 3 , [42,147,[163][164][165][166][167] AgClO 4 , [158,162] Cu(NO 3 ) 2 , [82,103,115,160,164,[168][169][170][171] Cu(CH 3 COO) 2 , [172] HAu-Cl 4 , [40,147,173,174] PtCl 4 , [42] and NiCl 2 . [147] Regarding reducing agents, polyvinylpyrrolidone (PVP) is a common choice, whose decomposition produces formic acid, able to reduce metal ion species.…”
Section: Laser-induced Reductionmentioning
confidence: 99%
See 1 more Smart Citation